STRATEGI DAN GAYA DEBAT GIBRAN DI PILPRES 2024 - Hamdi, Saipul (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The adoption of debates between presidential and vice presidential candidates is one of several campaigns for Indonesia's 2024 Presidential Election. This discussion is intended not only to introduce the candidate's thoughts and ideals, but also to demonstrate each candidate's ability to identify and solve societal problems. The candidates continue to make every effort to attend every invitation, both from the KPU and from other sources, such as campus debates or dialogues, religious organizations, national television, and non-governmental organizations (NGOs). What is intriguing is Gibran's work, which has received a lot of criticism from netizens, both supporters and opponents. In fact, many insinuations were made against Gibran on various social media platforms, prompting the use of the terms Samsul, belimbing sayur, plonga-plongo, and others. This essay seeks to comprehend Gibran's debate technique and style on the stage of the 2024 presidential election. The results revealed Gibran's practice of declining debate invitations outside of the KPU in order to keep his thoughts and views hidden from his political opponents. Gibran did admirably in the KPU debate, outperforming his debate opponent, who was expected to be brutally bullied by his more senior and experienced debate opponent. The abrasive debating style while being polite and the tricks used drew the attention of netizens on social media. This gimmick subsequently became viral on numerous social media platforms, and he was even referred to as a “suhu” rather than a “cupu”. This is a qualitative study conducted utilizing a desk study approach, which entails collecting and processing data from available sources such as websites and YouTube videos relating to the research's themes and issues.